2021
DOI: 10.3389/fendo.2021.666140
|View full text |Cite
|
Sign up to set email alerts
|

Single-Cell RNA Sequencing Reveals B Cells Are Important Regulators in Fracture Healing

Abstract: The bone marrow microenvironment is composed primarily of immune and stromal cells that play important roles in fracture healing. Although immune cells have been identified in mouse bone marrow, variations in their numbers and type during the fracture healing process remain poorly defined. In this study, single-cell RNA sequencing was used to identify immune cells in fracture tissues, including neutrophils, monocytes, T cells, B cells, and plasma cells. The number of B cells decreased significantly in the earl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 35 publications
1
22
0
Order By: Relevance
“…Both matrixes were generated by the same platform annotation chip, so we considered that there were no data differences between groups. GSE142786 matrix contains single-cell gene expression profiles derived from 2 samples from patients 0 days post-fracture and 30 days post-fracture (31). Details about these databases and samples can be found in Table 1.…”
Section: Data Downloaded and Pre-processingmentioning
confidence: 99%
“…Both matrixes were generated by the same platform annotation chip, so we considered that there were no data differences between groups. GSE142786 matrix contains single-cell gene expression profiles derived from 2 samples from patients 0 days post-fracture and 30 days post-fracture (31). Details about these databases and samples can be found in Table 1.…”
Section: Data Downloaded and Pre-processingmentioning
confidence: 99%
“…Circulating immune cells also influence bone states ( 56 , 57 ). Aging and impaired circulating monocytes were chemotactic to bone lesions.…”
Section: Discussionmentioning
confidence: 99%
“…In the meanwhile, a recent single-cell sequencing study revealed that skeletal muscle-derived mesenchymal progenitors also engage in bone repair, which will explain why adjacent tissues also matter ( Julien et al, 2021 ). In addition, Zhang H. et al (2021) suggest that B cells are key regulators of bone healing in the bone marrow microenvironment due to the opposite pattern between B cells and bone formation and resorption activities. Considering the fact that outcomes of bone defect healing are uncertain under the influence of different risk factors, such as age, nutritional status, and contamination degree ( Nicholson et al, 2021 ), we suspected that differences in the bone defect microenvironment may contribute to it.…”
Section: Bone Defect Microenvironment and Bone Healing Mechanismmentioning
confidence: 99%